EXPERIMENTAL STUDIES THERMOELECTRIC SYSTEMS FOR SHORT-TERM STORAGE AND TRANSPORTATION OF BIOLOGICAL MATERIAL - T. A. Ismailov; I. Sh. Mispahov; O. V. Evdulov; M. A. Hazamova (Вестник Дагестанского государственного технического университета: Технические науки)
Described a schematic diagram of an experimental stand thermoelectric system for shortterm storage and transportation of biological material. The technique of the pilot study of the thermoelectric system. The results of the pilot study.